2002
DOI: 10.3386/w9219
|View full text |Cite
|
Sign up to set email alerts
|

Boom-Bust Cycles in Middle Income Countries: Facts and Explanation

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 21 publications
(20 reference statements)
5
113
0
2
Order By: Relevance
“…Proceeding as in the proof of Lemma 4, I can show that (43) implies that the entrepreneur's utility is zero, contradicting the assumption that it is positive. Second, k * 0 > 0 and (43) imply that k * 1s > 0.…”
Section: Proof Of Propositionmentioning
confidence: 91%
See 1 more Smart Citation
“…Proceeding as in the proof of Lemma 4, I can show that (43) implies that the entrepreneur's utility is zero, contradicting the assumption that it is positive. Second, k * 0 > 0 and (43) imply that k * 1s > 0.…”
Section: Proof Of Propositionmentioning
confidence: 91%
“…By investing more in the first period the entrepreneur earns higher revenues if the good shock 1 For the main stylized facts on boom-bust cycles see Gourinchas, Valdes and Landerretche (2001), Borio and Lowe (2002), Bordo and Jeanne (2002), Tornell and Westermann (2002), Ranciere, Tornell and Westermann (2003). 2 See Borio (2003) and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…The stylized facts are now well known. A credit boom associated with a surge in capital flows precedes a sudden reversal which precipitates a credit crunch followed by a fall in real credit to the private sector (Tornell and Westerman, 2002;Schneider and Tornell, 2004). The evidence showed that lending booms leading to twin crisis were often preceded by capital account liberalization (Kaminsky and Reinhart, 1999;Demirguc-Kunt and Detragiache, 2005).…”
Section: Introductionmentioning
confidence: 95%
“…A number of studies employ statistical techniques, for example, Terrones (2008, 2012), Gourinchas, Valdes and Landarretch (2001), Barajas, Dell'Ariccia andLevchenko (2009), Tornell andWestermann (2002), IMF (2011), Dell'Ariccia et al (2012, and Arena et al (2015). They compare a country's credit-to-GDP ratio or real credit per capita to its nonlinear trend and determine the episodes of credit booms when the positive deviations from trend pass a certain threshold.…”
Section: Identification Of Credit Boom Episodesmentioning
confidence: 99%